Cytotoxicity study of four different varieties of patchouli essential oil - Nur Imani Fatihah, Mohamad Azman (2025)
Patchouli essential oil, derived from the leaves of Pogostemon cablin, holds potential due to its diverse therapeutic and pharmacological properties. The purpose of the study was to determine the cytotoxicity of essential oils extracted from four geographical varieties of patchouli (Kuala Pilah, Jerantut, Sri Makmur, and Paya Rambutan) using the hydro distillation method. The extracted oil colours were analysed using a microplate reader. Then, the compositions were analysed using Gas Chromatography-Mass Spectrometry (GC-MS), and their cytotoxicity was evaluated through the Brine Shrimp Lethality Assay (BSLA). The results showed variations in essential oil yield, chemical profiles, and cytotoxicity levels among the four varieties. Jerantut exhibited the highest cytotoxicity with an LC50 value of 5 µg/mL due to its high content of bioactive compounds like sesquiterpenes and gamma-Muurolene. This was followed by Sri Makmur and Paya Rambutan, with LC50 values of 28 µg/mL and 35 µg/mL, respectively. Lastly, Kuala Pilah demonstrated the lowest cytotoxicity with the highest LC50 value of 50 µg/mL. Colorimetric analysis revealed differences in oil intensity correlating with the chemical composition of each variation of patchouli essential oil. These findings suggest that the cytotoxicity and chemical composition of patchouli essential oils are primarily influenced by the genetic and varietal differences of the plants, even when grown under the same geographical and environmental conditions. This emphasizes the potential for targeted therapeutic and industrial applications based on specific patchouli varieties.